Preparação e caracterização de blendas elastoméricas totalmente verdes - Santos, Cláudio Henrique Chadu (2014)
In this work, blends of starch, carboxymethyl cellulose and hydroxypropyl methylcellulose with latex were produced and characterized according to their physicochemical properties. The blends were prepared in the proportions in percentage of 12.5%/87.5%; 25%/75%; 37.5%/62.5%; 50%/50%; 62.5%/37.5%; 75%/25%; 87.5%/12.5%. The characterization techniques used were Spectroscopy in the Infrared region Fourier transform (FTIR), scanning electron microscopy (SEM), Thermogravimetric Analysis (TGA) and Dynamic-Mechanical Analysis (DMA). The latex was collected in a farm located in the rural town of Silver - MG, and then immediately treated with ammonium hydroxide (NH4OH) to prevent clotting. The Hidroxipropilmetlcelulose, Carboximetlcelulose and starch polymers were solubilized in deionized water, and for the procedure with the starch was necessary warming of about 50 °C and shaking to its total dissolution. The FTIR analyzes revealed changes in band shift in the blends starch25%/latex75%, CMC50%/latex50% and in the other, changes in the intensity of the peaks in the spectra according to the variations in the proportions of the polymers in the blends. The SEM images generally show stages in the formation of mixtures of starch/latex and CMC/latex, and for HPMC/latex was more homogeneous structures indicating good compatibility. The results observed from TGA curves show that the addition of latex and hydroxypropyl starch in leads to a change in thermal stability of the resulting blends, while for the blends with carboxymethylcellulose no significant differences in the thermal stability. Dynamic-mechanical analysis showed an increased resistance of the blends, thus changing the properties of the films being shown in the values of E\' and Tanδ. The results showed that the blends of HPMC/latex have greater compatibility and miscibility in comparison with other mixtures investigated, discussing the limitations of pure film and the improvement of the properties of the blends obtained.